Microwave dielectric and attenuation properties of Ni0.7-xCoxZn0.3Fe2O4 thick films - Rendale, M. K.; Kulkarni, S. D.; Puri, Vijaya (Microelectronics International, 2009)
Purpose - The aim of this paper is to investigate permittivity of nano structured Ni0.7-xCoxZn0.3Fe2O4 thick films at microwave frequencies. Design/methodology/approach - Nanosized Ni0.7-xCoxZn0.3Fe2O4 ferrites with x = 0, 0.04, 0.08 and 0.12 were prepared by sucrose precursor technique using the constituent metal nitrates. Thick films of the ferrites were fabricated on alumina substrates by screen-printing technique. Microwave dielectric constant (epsilon') and the loss factor (epsilon `') for the thick films were measured by VSWR slotted section method in the 8-18 GHz range of frequencies. Microwave attenuation properties were studied using a waveguide reflectometer set up. Findings - Both the epsilon' and epsilon `' were found to vary with frequency and composition x It is observed that, value of epsilon' increases with increase in x, due to the increase in bulk density and reduction in porosity of the material, that resulted due to the substitution of cobalt in Ni-Zn ferrite. The microwave transmission loss offered by the thick films was found to increase with the increase in cobalt concentration x Within the band width of 4 GHz (from 12-16 GHz), all the films except that with x = 0.04 offered the reflection loss of less than 3 dB. Originality/value - The dielectric constant of Ni0.7-xCoxZn0.3Fe2O4 thick films have been reported for the first time. These thick films provide scope for cost effective planar ferrite devices.
Keywords: Microwaves; Oxides; Thick-film circuits